Women in Tourism: Comparitive Findings and Policy Recommendations from Bali and Jakarta - Ni Made Ary Widiastini; Ni Wayan Giri Adnyani; Ni Luh Putu Agustini Karta; Dini Anggraeni Sirad; Putu Indah Rahmawati (Universitas Pendidikan Ganesha, 2025)
Women play a significant role in the tourism industry in Bali and Jakarta. Disparities persist in access, leadership, and wages despite their high involvement in hotels, MICE, the creative economy, and micro-enterprises. This study aims to compare the roles of women in Bali and Jakarta, identify factors influencing their involvement, and assess adaptation strategies to work and domestic demands. The study employed mixed methods. Quantitative data were obtained through surveys of hotel managers in Bali and Jakarta. Qualitative data were collected through in-depth interviews with hotel managers and observations of operational activities. Women in Bali are more dominant in the creative economy sector, with strong local community support. Women in Jakarta are more likely to work in the formal sector, with broader access to training but still face barriers to promotion to managerial positions. Wage inequality persists in both regions. Women embrace flexible working hours, family support, and business diversification to maintain economic stability. These findings underscore the need for gender-friendly tourism policies, expanded access to professional training, provision of childcare services, and increased women's involvement in tourism decision-making. This study contributes to gender and tourism studies by integrating social capital and economic resilience perspectives in a cross-context urban-cultural comparison.